190k views
0 votes
Estimate the limit.
Picture below

Estimate the limit. Picture below-example-1
User Plokko
by
5.4k points

2 Answers

3 votes

Answer:

Hence, the limit of the expression:


\lim_(x \to 3) (x-3)/(x^2-2x-3) is:


(1)/(4)

Explanation:

We have to estimate the limit of:


\lim_(x \to 3) (x-3)/(x^2-2x-3)

We can also represent the denominator of the function in the limit as:


x^2-2x-3=x^2-3x+x-3\\\\x^2-2x-3=x(x-3)+1(x-3)\\\\x^2-2x-3=(x+1)(x-3)

Hence, we have to estimate the limit of:


\lim_(x \to 3) (x-3)/((x+1)(x-3))\\\\= \lim_(x \to 3)(1)/(x+1)\\ \\=(1)/(3+1)\\\\=(1)/(4)

Hence, the limit of the expression:


\lim_(x \to 3) (x-3)/(x^2-2x-3) is:


(1)/(4)

User Quickthyme
by
5.8k points
1 vote

Answer:

Choice C is correct answer.

Explanation:

We have given expression.


\lim_(x \to \ 3) x-3/x^(2) -2x-3

We have to find the limit of function.

Simplifying the denominator, we have

x²-2x-3

Factoring the above expression, we have

(x-3)(x+1)


\lim_(x \to \ 3) (x-3) / (x-3)(x+1)


\lim_(x \to \ 3) 1/x+1

1 / 3+1

1/4

0.25

hence,
\lim_(x \to \ 3) x-3/x^(2) -2x-3 = 0.25

User UberNeo
by
4.8k points